The vicious cycle of functional neurological disorders: a synthesis of healthcare professionals' views on working with patients with functional neurological disorder. Issue 10 (8th May 2022) - Barnett, Caroline; Davis, Rebecca; Mitchell, Claire; Tyson, Sarah
Abstract: Purpose: The objective of this review was to synthesise studies which address the views of healthcare professionals (HCPs) towards patients with functional neurological disorder (FND). Methods: An interpretive systematised review was conducted. Seven databases were searched using a comprehensive search strategy (MEDLINE, EMBASE, AMED, CINAHL, PsychINFO, ProQuest Nursing and Allied Health, and Scopus). Qualitative studies and those using survey methods were included. An inductive approach to thematic analysis was used to identify concepts from the data and to synthesise the results. Results: The views of 2769 HCPs were represented in 11 included articles. The overarching theme across the articles was uncertainty: about making the diagnosis of FND, about professional roles, and about optimum management. Fear was also a common theme: of saying the wrong thing, of offending patients, or of breaking the therapeutic relationship. Conclusions: If all HCPs felt uncertain about how to manage patients with FND and avoided them by passing them on to another discipline, then a "vicious cycle" is formed in which patients are passed from one professional to another but without receiving clear, honest information, or effective treatment. HCPs would benefit from increased training on FND and clear clinical pathways to alleviate feelings of uncertainty. Implications for rehabilitation: Evidence-based or, at the very least, consensus-based multi-disciplinary care pathways for the assessment and treatment of patients with functional neurological disorder are required to improve equitability of services. Training packages for healthcare professionals need to be developed, evaluated and implemented in order to improve confidence of making and explaining the diagnosis and to reduce stigma of functional neurological disorders. Improved input for patients with functional neurological disorder is likely to occur if healthcare professionals are open, honest and use effective communication skills, both with their patients and fellow healthcare professionals.